Limitation of life support techniques at admission to the intensive care unit: a multicenter prospective cohort study - Olga Rubio; Anna Arnau; Sílvia Cano; Carles Subirà; Begoña Balerdi; María Eugenía Perea; Miguel Fernández-Vivas; María Barber; Noemí Llamas; Susana Altaba; Ana Prieto; Vicente Gómez; et al. (Journal of Intensive Care, 2018)
Abstract Purpose To determine the frequency of limitations on life support techniques (LLSTs) on admission to intensive care units (ICU), factors associated, and 30-day survival in patients with LLST on ICU admission. Methods This prospective observational study included all patients admitted to 39 ICUs in a 45-day period in 2011. We recorded hospitals’ characteristics (availability of intermediate care units, usual availability of ICU beds, and financial model) and patients’ characteristics (demographics, reason for admission, functional status, risk of death, and LLST on ICU admission (withholding/withdrawing; specific techniques affected)). The primary outcome was 30-day survival for patients with LLST on ICU admission. Statistical analysis included multilevel logistic regression models. Results We recruited 3042 patients (age 62.5 ± 16.1 years). Most ICUs (94.8%) admitted patients with LLST, but only 238 (7.8% [95% CI 7.0–8.8]) patients had LLST on ICU admission; this group had higher ICU mortality (44.5 vs. 9.4% in patients without LLST; p < 0.001). Multilevel logistic regression showed a contextual effect of the hospital in LLST on ICU admission (median OR = 2.30 [95% CI 1.59–2.96]) and identified the following patient-related variables as independent factors associated with LLST on ICU admission: age, reason for admission, risk of death, and functional status. In patients with LLST on ICU admission, 30-day survival was 38% (95% CI 31.7–44.5). Factors associated with survival were age, reason for admission, risk of death, and number of reasons for LLST on ICU admission. Conclusions The frequency of ICU admission with LLST is low but probably increasing; nearly one third of these patients survive for ≥ 30 days.